A method for measuring negative ion density distribution using harmonic currents in a low-pressure oxygen plasma. (29th June 2020) - Zhang, Aixian; Kwon, Deuk-Chul; Chung, Chin-Wook
Abstract: This work investigates the negative ion density via the floating harmonic method (FHM) in an oxygen inductively coupled plasma (ICP). When a small sinusoidal voltage is applied to the specific potentials of a planar Langmuir probe, harmonic currents will be generated by the sheath nonlinearity. Using harmonic current analysis, it is possible to obtain the positive ion currents, electron currents and electron temperatures within the plasma. One probe potential is set to floating and the other is kept in the range between the floating potential and the plasma potential. From the current ratios of positive ions to electrons, the electronegativity and modified pre-sheath potential can be deduced, thereby obtaining the negative ion density from the quasi-neutrality. The variations in the negative ion density and electronegativity distributions at various gas pressures and applied powers are compared with those of a two-dimensional fluid model incorporating electron heating kinetics and those found using a two-probe method in reference Chabert et al (1999 Plasma Source Sci . Technol . 8 561).